2016
DOI: 10.1007/s00894-016-3195-6
|View full text |Cite
|
Sign up to set email alerts
|

DFT and TDDFT investigation of the Schiff base formed by tacrine and saccharin

Abstract: Schiff bases have many chemical and biological applications in medicine and pharmaceuticals due to the presence of an imine group (-C=N-). These bases are used in many different fields of technology, and in photochemistry because of their photochromic properties. Here, the structural and electronic properties of the Schiff base formed by tacrine and saccharin (TacSac) were explored using density functional theory with the B3LYP, M06-2X, M06L, and ωB97XD functionals in combination with the 6-311++G(d,p) basis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…hydrogen bonding) between solute and solvent molecules. Interestingly, inclusion of nonelectrostatic terms to IEF-PCM by SMD approach does not show any significant changes in the geometries in contrast to our former results [41]. It may be concluded that steric factors dominate over all other possible factors effecting geometries for the investigated systems.…”
Section: Resultscontrasting
confidence: 76%
See 4 more Smart Citations
“…hydrogen bonding) between solute and solvent molecules. Interestingly, inclusion of nonelectrostatic terms to IEF-PCM by SMD approach does not show any significant changes in the geometries in contrast to our former results [41]. It may be concluded that steric factors dominate over all other possible factors effecting geometries for the investigated systems.…”
Section: Resultscontrasting
confidence: 76%
“…3. In our former DFT study [41], our results indicate that formation of the TacSac complex requires energy (EC values vary between +5 to +12 kcal/mol) and is a nonspontaneous endergonic process with ΔΔG values around +10 kcal/mol. However, in current study, MP2 results revealed a quite oppposite tendency.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations